The Influence of Honey Wound Dressing Using a Post Trauma Wound at Bandung Adventist Hospital - Rumbay, Gabriela Gloria; Anderson, Elisa (8ISC Abstract Proceedings; 8ISC Abstract Proceedings, 2022)
Honey wound dressing is one of the special dressings used for wounds in the process of wound healing. Bandages of honey are known to be very effective in the process of healing wounds because of their low water content, and the PH of honey in the dressing of acid honey and its hydrogen peroxide content can kill bacteria, fungi, viruses, and microorganisms that enter the human body so that infecting wounds one of which is trauma injury. The purpose of this study was to determine the effect of the use of honey as a wound dressing on post-traumatic wounds at Bandung Adventist Hospital. The method that was used in this research is quantitative by using a pre-experiment one group pretest-posttest design research design with statistical analysis. The sampling technique used purposive sampling with an overall 45 of total with trauma wound at the Adventist Clinic Hospital in Bandung, and the data were collected using the Bates Jensen Wound Assessment Tool and analyzed using the Wilcoxon test. The results obtained P-value = 0,000 <0.05, so it was concluded that there is an influence on the use of a honey wound dressing on post-traumatic wounds at Bandung Adventist Hospital. Recommendation for the hospital institutions to continue to use this intervention in wounds, not just in post-traumatic wounds, and hopefully, the wider community can further apply the results of this research in everyday life. Keywords : Honey, wound-dressing, post-traumatic, injury